An integrated sea-land approach for analyzing forms, processes, deposits and the evolution of the urban coastal belt of Cagliari. Issue 4 (28th July 2021) - Porta, Marco; Buosi, Carla; Trogu, Daniele; Ibba, Angelo; De Muro, Sandro
ABSTRACT: Using a comprehensive cartographic product, this paper aims to illustrate the evolution of the urban geomorphological setting of the urban coastal belt of Cagliari (southern Sardinia, Italy, western Mediterranean Sea). The geomorphological map (1:14, 000) presented herein summarizes different data (e.g. urban development, anthropogenic features, geomorphological elements, recent deposits, sedimentological distribution, hydrodynamics and ecological components) acquired through an integrated sea-land approach and a multidisciplinary-multitemporal investigation. The main significant environmental changes are linked to urbanization, the development of port infrastructures (embankments along the shoreline and the construction of the canal harbour), remediation work and filling activities, and the hardening of dune and beach systems and cliffs. These man-made interventions have increased the vulnerability of the shore zones to flood hazards and risks, which are linked to sea-level rises and global warming.